RESILIENCE IN NURSING STUDENTS: PSYCHOSOCIAL CHALLENGES AND STRENGTHENING STRATEGIES IN THE UNIVERSITY CONTEXT - Engel, Ana Maria Rita Pedroso Vilela Torres de Carvalho; de Carvalho, Stela Regina Pedroso Vilela Torres; Ferreira, Diego Mariozi; Custódio, Flávia Cristina; Menezes, João Daniel de Souza; da Silva, Matheus Querino; Stefani, Andressa Karina; Lázaro, Camila Aline; Martinez, William Donegá; dos Santos, Loiane Letícia; Brienze, Vânia Maria Sabadoto; André, Júlio Cesar (Seven Editora, 2026)
Nursing education is a challenging journey, demanding from students not only technical knowledge but also psychosocial robustness. This chapter explores the levels of resilience and their determinants in incoming nursing students at a higher education institution, aiming to understand how sociodemographic factors and the various dimensions of resilience are interconnected. An observational, cross-sectional, and quantitative study was conducted with 104 academics, utilizing a Sociodemographic Variables Questionnaire and the Wagnild and Young Resilience Scale. The results indicated that most students exhibit moderate resilience; however, a significant portion demonstrated reduced levels. Gender identity and employment status were identified as sociodemographic variables significantly associated with resilience. While personal competence and self-acceptance emerged as strengths, independence, determination, self-confidence, and adaptability were areas requiring further development. These findings underscore the need for personalized psychosocial support programs, focused on strengthening resilience and addressing students’ specific needs, thereby contributing to the training of professionals better equipped to face the complexities of healthcare practice.